Immigration and the labor market in the post-pandemic recovery - Kristin F. Butcher; Lucas Cain; Camilo García Jimeno; Ryan Perry (Federal Reserve Bank of Chicago, 2023)
Standard estimates based on the main household survey used to shed light on labor markets -the Current Population Survey (CPS)- suggest that after a significant drop during the pandemic, recent rapid growth has brought the foreign-born population back to, or above, levels predicted by the pre-pandemic trend. However, we document that the weighting factors used to make the CPS nationally representative have recently displayed some unusual movements and conclude that standard estimates of the foreign-born population may currently be too high. We also show that recent labor market indicators are inconsistent with increased foreign-born induced slack.
Keywords: 330